Total synthesis of (S)‐(+)‐ent‐phomapyrones B and surugapyrone B. (11th December 2019) - Ohmukai, Hiroaki; Sugiyama, Yasumasa; Hirota, Akira; Kirihata, Mitsunori; Tanimori, Shinji
Abstract : Abstract: Phomapyrone B (1 ), the 2‐pyrones isolated from the phytopathogenic fungus Leptosphaeria maculans, has been synthesized as the enantiomeric form starting from ( S )‐2‐methylbutanol (4 ). Surugapyrone B (3 ) isolated from Streptmyces sp. USF‐6280 as an antioxidant has also been synthesized as a natural form. The absolute configuration of phomapyrone B (1 ) was estimated to be the ( R )‐form and that of surugapyrone B (3 ) being the ( S )‐form. A series of 2‐pyrone derivatives 17 have been synthesized through the established procedure and their DPPH radical‐scavenging activities have also been evaluated.